ANALISIS PENGARUH CORPORATE GOVERNANCE DAN ROA TERHADAP STRUKTUR MODAL DENGAN VARIABEL KONTROL TANGIBILITY ASSET DAN MARKET TO BOOK RATIO (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2016) - Wahyu Sulistyanto, Bismo; Demi Pengestuti, Irene Rini (Diponegoro Journal of Management, 2018)
This study aimed to analyze the effect of Firm Age, Board of Director, Audit Committee Meeting, Ownership Concentration and ROA (Return on Assets) on the Capital Structure that is projected as DER (Debt Equity Ratio) with Tangibility Asset and Market to Book Ratio as control variable .            The population used in this study is a Manufacturing Firm listed in the Indonesia Stock Exchange in 2012-2016. The sampling technique used is purposive sampling which obtained 35 firms. The analytical method used is a classic assumption test such as Normality Test, Autocorrelation Test, Multicollinearity Test, Heterocedasticity Test,  Determination Coefficient  Test, F Statistical Test, T Statistical Test and Multiple Regression Analysis.            The result showed that the Firm Age, Audit Committee Meeting and Market to Book Ratio have a significant positive effect on DER (Debt Equity Ratio). While the Board of Director, Ownership Concentration, ROA (Return on Assets) and Tangibility Asset  have a significant negative effect on DER (Debt Equity Ratio). The result from determination coefficient  of 0.529 shows that 52.9% of the DER variation is explained by the independent variables in the study, while the remaining 47.1% is explained by other variables not included in the research model.